2011
DOI: 10.1183/09031936.00105010
|View full text |Cite
|
Sign up to set email alerts
|

Infant antibiotic use and wheeze and asthma risk: a systematic review and meta-analysis

Abstract: Our aim was to systematically review and meta-analyse longitudinal studies on antibiotic use and subsequent development of wheeze and/or asthma with regards to study quality, outcome measurement, reverse causation (RC; wheezing/asthma symptoms have caused prescription of antibiotics) and confounding by indication (CbI; respiratory tract infections leading to antibiotic use may be the underlying cause triggering asthma symptom development).English-language papers and studies published before November 1, 2010 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
4
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 56 publications
3
108
4
6
Order By: Relevance
“…On the basis of earlier findings, antibiotic use early in life may alter the normal immune system development in a critical window during which specific subsets of the infant gut microbiota can differentially regulate immune function, leading to an influence on the likelihood of developing atopic disorders (28,29). On the other hand, in contrast with the current survey, a meta-analysis conducted by Pander et al on longitudinal studies indicated that a weak association could exist between antibiotic use and subsequent development of wheeze/asthma over 5 -6 years of age (30). Moreover, the findings of Celedon et al did not support the hypothesis that exposure to antibiotics in the first year of life is related to the later development of asthma, AR, and eczema symptoms or diseases at the age of 5 (31).…”
Section: Discussioncontrasting
confidence: 68%
“…On the basis of earlier findings, antibiotic use early in life may alter the normal immune system development in a critical window during which specific subsets of the infant gut microbiota can differentially regulate immune function, leading to an influence on the likelihood of developing atopic disorders (28,29). On the other hand, in contrast with the current survey, a meta-analysis conducted by Pander et al on longitudinal studies indicated that a weak association could exist between antibiotic use and subsequent development of wheeze/asthma over 5 -6 years of age (30). Moreover, the findings of Celedon et al did not support the hypothesis that exposure to antibiotics in the first year of life is related to the later development of asthma, AR, and eczema symptoms or diseases at the age of 5 (31).…”
Section: Discussioncontrasting
confidence: 68%
“…In a large population-based registry, ÖRTQUIST et al [17] found a positive association between prenatal antibiotic exposure and asthma in the offspring, but these findings were not confirmed in a sibling analysis, indicating a confounding role of shared familial factors. Similarly, two meta-analyses attributed a positive association between antibiotic exposure in infancy and subsequent asthma to confounding factors [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by not having to select for specific microorganisms, as is the case when culture-or hybridization-based approaches are employed, one could generate an overall profile of the impact of antibiotics on infant gut microbiota. While the studies to date are significant, and it is notable that a recent meta-analysis of 18 studies also found a weak positive association between antibiotic use in infancy and asthma and wheeze risk (OR 1.27 95% CI: 1.12-1.43), 177 there are a number of other studies, such as that by Celedon et al that failed to reveal the existence of an association. Similarly in 2007, the Koala Birth Cohort Study of over 2,700 families, once more failed to demonstrate any association between antibiotic use and eczema or asthma risk.…”
mentioning
confidence: 89%